A conceptual paper on Malay language teachers disposition - Anamala, Gaytri; Abd Rahman, Fadzilah (Zes Rokman Resources, 2016)
This is a conceptual paper to study the Malay language teachers’ disposition. The study reviews literature on concept of disposition and explains the importance of Malay language teachers’ disposition towards students in the teaching and learning of Malay language in the secondary school classroom. The Malaysian National Education Philosophy focuses in forming responsible citizens who are balanced intellectually, spiritually, emotionally and physically. In order to be aligned with that, teachers should have a good disposition. Teachers should strive to develop quality character by having elements of a good disposition as teachers have a significant impact in the classroom and play an important role in educating the younger generation. Therefore, Malay language teachers play an important role to shape students during the teaching and learning of Malay language. Do the Malay language teachers have a good disposition in achieving this important aspiration? There were allegations that many Malay language teachers meet the requirements of subject content knowledge and pedagogical skills, but lack of good practice in implementing the disposition in classroom. Besides not practicing good disposition, most teachers are also not aware of the concept and importance of disposition. Teachers play the role of a model where students always see and emulate the attitude and perception of teachers. Students would make impressions on their teachers consciously or unconsciously. Clearly, the disposition of a good teacher allows students interested in the personality of the teacher and so willing to listen and follow the lesson. Therefore, this conceptual paper analyzes the importance of Malay language teachers’ disposition in teaching and learning of Malay Language.